The Encyclopedia of Medical Robotics 2018
DOI: 10.1142/9789813232266_0008
|View full text |Cite
|
Sign up to set email alerts
|

Snake-Like Robots for Minimally Invasive, Single-Port, and Intraluminal Surgeries

Abstract: The surgical paradigm of Minimally Invasive Surgery (MIS) has been a key driver to the adoption of robotic surgical assistance. Progress in the last three decades has led to a gradual transition from manual laparoscopic surgery with rigid instruments to robot-assisted surgery. In the last decade, the increasing demand for new surgical paradigms to enable access into the anatomy without skin incision (intraluminal surgery) or with a single skin incision (Single Port Access surgery -SPA) has led researchers to i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 164 publications
0
21
0
Order By: Relevance
“…(8) was then solved for eachg c i to write a nonlinear statetransition expression as shown in Eq. (9). Here, w m indicates the applied magnetic wrench that is estimated via the dipole model; this is possible owing to localization feedback of IM pose and kinematic feedback of the serial manipulator that is used to obtain EM pose.…”
Section: Estimation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(8) was then solved for eachg c i to write a nonlinear statetransition expression as shown in Eq. (9). Here, w m indicates the applied magnetic wrench that is estimated via the dipole model; this is possible owing to localization feedback of IM pose and kinematic feedback of the serial manipulator that is used to obtain EM pose.…”
Section: Estimation Methodsmentioning
confidence: 99%
“…The modelling of continuum devices has been thoroughly investigated where kinematic or mechanics-based computations rely on computing the configuration of a device given a known robot base, e.g. physical point where robot is at least partially constrained, and applied loads [9]- [12]. Similar methods have been applied for continuum devices that rely on magnetic fields for actuation [5], [6], [13].…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we briefly present an overview of the mechanical architectures used to the extent needed to outline their associated modeling and control challenges. A more detailed review of these robotic architectures can be found in [25]. High dexterity snake-like robot architectures are typical in systems designed for NOTES and SPA.…”
Section: Surgical Systems For Notes and Single Port Access Surgerymentioning
confidence: 99%
“…Continuum robots, defined as actuated structures whose constitutive materials form curves with continuous tangent vectors, have found numerous applications within surgical procedures [14], [15]. Examples include concentric tube robots/active cannulas [16], [17] and multi-backbone continuum robots [18], [19] for trans-oral upper airway surgery [20], single port access surgery [21], [22], minimally invasive surgery (MIS) [23], and arthroscopy [24].…”
Section: Introductionmentioning
confidence: 99%